Green preparation of branched biolubricant by chemically modifying waste cooking oil with lipase and ionic liquid. (20th November 2020) - Zhang, Wei; Ji, Hairui; Song, Yanliang; Ma, Sen; Xiong, Wei; Chen, Changjing; Chen, Biqiang; Zhang, Xu
Abstract: To reduce the environment pollution from biolubricant synthesis, in this study, we developed a green and efficient strategy for the preparation of octylated branched biolubricant from waste cooking oil (WCO): (1) WCO was first hydrolyzed by a lipase ( Candida sp. 99–125 ) to produce unsaturated fatty acids (UFAs), the latter was subsequently concentrated by urea complexation; (2) Next, we synthesized new esters using the UFAs as substrate via esterification with 2-ethylhexanol employing lipase (Novozym 435) and the new esters products were further epoxidated; (3) After that, the epoxy group was attacked by a low-cost nucleophilic reagent, octanoic acid, to prepare octylated branched biolubricant using an recyclable ionic liquid, [HMIm][PF6 ], as catalyst. After three recycling times, [HMIm][PF6 ] remained catalytic activity with a conversion yield of 81.22% and selectivity of 82.10%. The obtained product showed excellent lubricant properties, such as low pour point of −61 °C, high viscosity index of 149 and high thermal-oxidation stability (onset temperature of 326.35 °C and oxidative onset temperature of 312.06 °C). The high frequency reciprocating rig (HFRR) measurement demonstrated that lubrication performance (friction coefficient of 0.09 and wear spot diameter of 203 μm) was much better than that of mineral based lubricant with the same viscosity grade. Therefore, this study provided a critical synthetic strategy for preparing high-performance biolubricants from WCO. Graphical abstract: Image 1 Highlights: An innovative strategy of biolubricant preparation from waste cooking oil was proposed. Modification on unsaturated sites catalyzed by lipases and ionic liquid. [HMIm][PF6 ] remained high stabilization after three recycling times. Biolubricant exhibited excellent pour point, thermo-oxidative stability and lubrication performance.